2021
DOI: 10.3390/su13031433
|View full text |Cite
|
Sign up to set email alerts
|

Stress on Frontline Employees from Customer Aggression in the Restaurant Industry: The Moderating Effect of Empowerment

Abstract: In service industries such as restaurants, abusive customer (jay-customer) behaviors may evoke emotional exhaustion and burnout in frontline employees, threatening job satisfaction as well as sustainable management in the hospitality industry. Therefore, there is a need to identify whether (and to what degree) such customer behaviors stress frontline employees enough to affect their mental health, which may lead to employee turnover. To understand jay-customer behaviors in a restaurant setting, this study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 72 publications
(160 reference statements)
1
12
0
8
Order By: Relevance
“…Our contribution to dark side and inappropriate communication frames is to connect to organizational violence [ 44 ] to theorize how both relationships and organizational structures can sustain harassment, bullying, and other forms of violence at work. In particular, our research adds to ongoing scholarship on how violence is normalized in certain occupations [ 49 , 50 , 51 ], showcasing a need for continued research at an occupational level. We suggest future scholarship to theorize occupational violence, which we conceptualize as how members of specific occupations create, maintain, or challenge communication practices and norms that structure the normativity of violence at work.…”
Section: Contributions and Future Directionsmentioning
confidence: 96%
See 3 more Smart Citations
“…Our contribution to dark side and inappropriate communication frames is to connect to organizational violence [ 44 ] to theorize how both relationships and organizational structures can sustain harassment, bullying, and other forms of violence at work. In particular, our research adds to ongoing scholarship on how violence is normalized in certain occupations [ 49 , 50 , 51 ], showcasing a need for continued research at an occupational level. We suggest future scholarship to theorize occupational violence, which we conceptualize as how members of specific occupations create, maintain, or challenge communication practices and norms that structure the normativity of violence at work.…”
Section: Contributions and Future Directionsmentioning
confidence: 96%
“…Icenogle et al’s [ 50 ] discovery further illustrates the need for additional research on sexual harassment within non-white-collar occupations, such as our own. Bi et al [ 51 ] (p. 11) specifically examined organizational violence of service industry customers in South Korea, and their survey results revealed that restaurant employees faced verbal and physical abuse and sexual harassment by customers. Such repeated abuse by customers led to burnout and health impacts [ 51 ] (p. 12).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The deviant behavior of these customers disrupts service encounters, decreases other customers' overall service satisfaction [8,9], and damages the service companies' financial performance [10], which is called dysfunctional customer behavior [11]. Previous service management research has found that such dysfunctional customer behavior adversely affects service employees, generating psychological stress, damaging their self-esteem, and making the service employees engage in counterproductive behaviors [6,12,13]. On the other hand, dysfunctional customer behavior in a service setting is considered a dirty little secret despite the number of known issues.…”
Section: Introductionmentioning
confidence: 99%